Antecedent Of Extent Of Accounting Information Usage And The Influence Of Accounting Information Usage On Financial Performance. - Abdullah, Noorsham Suhaida (Universiti Sains Malaysia, 2008)
Small and Medium Enterprises are the backbones on Malaysian economy. Studies have indicated that SMEs encounter financial difficulties due to major internal weaknesses in financial management of the businesses. This study examines the extent of usage of accounting information and types of accounting information that used by SMEs. This study also examines whether specific organizational characteristic and entrepreneur characteristics such as gender, education level, accounting training, and entrepreneurial traits have positively relation to the extent of accounting information used. This study was done on selected small businesses in Seberang Perai Tengah Pulau Pinang. The result from this research supported the relationship whereby education level to be positively related to the extent of accounting information used.